Preview-Review Bilingual Instructional Tools Development with Discovery Learning Model Setting to Enhancing Student’s Conceptual Understanding and Speaking Ability - Priyanka, Luh Mitha; Selamat, I Nyoman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aimed to analyze the validity categories and the effectiveness of preview-review bilingual instructional tools with discovery learning model setting in enhancing conceptual understanding and speaking ability. This study was research and development (R & D) using ADDIE developmental model consisting of analyzing, design, develop, implementation, and evaluation. The data collection was done through non-test techniques using product validation sheets, learning observational sheet, and observational sheet for speaking ability and test techniques using an assessment sheet for measuring conceptual understanding. The validity of preview-review bilingual instructional tools with discovery learning model setting was analyzed qualitatively based on 5-point scale conversion table. The effectiveness of preview-review bilingual instructional tools with discovery learning model setting in the implementation stage was analyzed based on the average of the gain score. The result showed that the validity of preview-review bilingual instructional tools with discovery learning model setting was 3.60 for the content and 3.55 for the language which is in very good category and the developed of preview-review bilingual instructional tools with discovery learning model setting was effective in enhancing conceptual understanding and speaking ability based on average gain score.